Research on enhanced channel assignment scheme in wireless mesh network - Lin-han FENG; Zhi-hong QIAN; Dong-cheng JIN (Tongxin xuebao)
To ensure the reliability of the wireless mesh network resource assignment,an interference model to node traffic model of WMN was introduced,and channel assignment strategy based on fixed traffic-awareness C-HYA channel assignment strategy was improved,which a greedier algorithm to avoid ripple effect and reduce network interference was adopted.In addition,the network topology and simulates the algorithm was built.The results of theoretical analysis and simulation show the performance of improved channel assignment strategy compared with traditional algorithm in terms of resisting ripple effect and channel interference.